PENGARUH KINERJA GURU DAN LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA SDK PENABUR BANDARLAMPUNG - Manullang, Nita Tifani (Jurnal Manajemen Magister Darmajaya, 2016)
The study aimed to determine the effect of the teachers performance towards students learning motivation, the effect of the school environment towards students learning motivation, and the effect of the teachers performance and the school environment towards students learning motivation in SDK Penabur Bandarlampung. The samples were students in SDK Penabur Bandarlampung of first until sixth grade. They were 76 students. The samples were taken by proportional random sampling technique using questionnaire. The results of the study explained that the study supported the hypothesis that the teachers performance partially affected significant towards students learning motivation, the school environment partially affected significant towards students learning motivation, and both the teachers performance and school environments significantly affected towards students learning motivation in SDK Penabur Bandar Lampung. The results were expected to give information and suggestion for teachers. Teachers should understand the teaching methods well or ways of teaching in accordance with students. In order to motivate the students, teachers should be more listening and responding to students suggestions and ideas. Â Keywords:Â  the Teachers Performance, the School Environment, Students Learning Motivation